2021
DOI: 10.3389/fnut.2021.676035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Tryptophan on Growth, Intestinal Microbiota, and Intestinal Gene Expression in an Improved Triploid Crucian Carp

Abstract: Tryptophan (Trp) has received increasing attention in the maintenance of intestinal function. In this study, improved triploid crucian carp (ITCC) fed diets containing 6.35 g kg−1 Trp had higher average daily gain (ADG) and improved villus height (VH) and crypt depth (CD) in the intestine compared to the control group. To elucidate the potential mechanisms, we used RNA sequencing (RNA-seq) to investigate changes in the intestinal transcriptome and 16S rRNA gene sequencing to measure the intestinal microbiota i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…× common carp ( Cyprinus carpio L.) allotetraploid hybrids (♂) with the diploid Japanese crucian carp (♀) ( Carassius auratus cuvieri T. et S.) ( Chen et al, 2009 ). Because of its advantages of fast growth speed, strong stress tolerance and delicious flesh quality, ITCC is the preferred species of crucian carp in freshwater aquaculture in China ( Fu et al, 2021 ). Up to now, some studies have reported that Hyp can promote growth and improve muscle quality in carnivorous marine fish, whereas Hyp’s potential for the same effect on omnivorous freshwater fish remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…× common carp ( Cyprinus carpio L.) allotetraploid hybrids (♂) with the diploid Japanese crucian carp (♀) ( Carassius auratus cuvieri T. et S.) ( Chen et al, 2009 ). Because of its advantages of fast growth speed, strong stress tolerance and delicious flesh quality, ITCC is the preferred species of crucian carp in freshwater aquaculture in China ( Fu et al, 2021 ). Up to now, some studies have reported that Hyp can promote growth and improve muscle quality in carnivorous marine fish, whereas Hyp’s potential for the same effect on omnivorous freshwater fish remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that most of the retained tryptophan (±48%) was found in the gut, which was also observed in Senegalese sole juveniles [19]. This may be due to tryptophan being the precursor of 5-hydroxytryptophan, which in turn is the precursor of serotonin, a hormone mainly synthesised in the gastrointestinal tract [11,34], or due to the beneficial effects of tryptophan in the intestinal structural integrity of fish [35].…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, oral CGA also had a positive effect on the density and height of the intestinal villi of Carassius auratus. The density and height of villi in the intestine can increase the contact area between the intestine and intestinal contents, thus increasing the deposition of nutrients, Frontiers in Microbiology 08 frontiersin.org which is of great significance for improving the health of animals (Fu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%